Commentary to the paper: A child of two mothers: what about the father? Italian overview - Di luca, Alessandro (Acta Biomedica Atenei Parmensis, 2021)
Assisted reproductive techniques have made it possible for same-sex couples to become "parents", and for children to have two mothers, or even two fathers. Such parents have applied for the legal registration of the birth certificates issued abroad for children born through assisted procreation procedures that would not have been legally possible in Italy. The Italian Constitutional Court and the Supreme Court of Cassation have however ruled against such recognition, pointing out that the children's best interest can be pursued through adoption "in extraordinary circumstances", as regulated by law n. 184, enacted in 1983. The article's Author has stressed the need for  new piece of legislation, specifically aimed at more effectively regulating such scenarios. We share that sentiment, and wholeheartedly hope that Italian lawmakers will soon draw up and enact a new law, based on adoption in exceptional circumstances, so that children born abroad through assisted reproduction may be allowed to live in a loving family settings, raised by the parents who made their births possible in the first place. Such new norms will have to ensure that the children's well-being and fundamental rights are upheld, including the right to know their biological origins.